Right ventricle-pulmonary artery coupling in repaired tetralogy of fallot with pulmonary regurgitation: clinical implications. (4th February 2022) - Panaioli, E; Birritella, L; Graziani, F; Lillo, R; Grandinetti, M; Di Molfetta, A; Przybyleka, B; Lombardo, A; Lanza, G; Secinaro, A; Perri, G; Amodeo, A; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background The right ventricle-pulmonary artery (RV-PA) coupling is a strong prognostic marker in several clinical settings, but only few studies focused on its role in repaired Tetralogy of Fallot (rToF) with pulmonary regurgitation (PR). Aim of this study was to assess whether differences exist in RV-PA coupling, estimated as by echocardiography, between patients with rToF and PR with (i-PVR) or without (ni-PVR) indication for pulmonary valve replacement (PVR). 3 Materials and Methods The study population included 40 rToF patients allocated to two groups: 20 i-PVR and 20 ni-PVR; 40 healthy controls were also included. All subjects underwent echocardiogram, while Cardiac magnetic resonance (CMR) was available in 27/40 rToF patients. RV-PA coupling was assessed by echocardiographic TAPSE/PASP and RV stroke volume/RV end systolic volume (RVSV/RVESV) by CMR. Results TAPSE was similar in i-PVR vs ni-PVR (19.0 ± 3.4 vs 18.8 ± 2.7 mm, p = 0.85) while RV-PA coupling was significantly worse in i-PVR vs ni-PVR (TAPSE/PASP 0.8 ± 0.3 vs 1.1 ± 0.5 mm/mmHg, p = 0.009) as well as in i-PVR vs controls (p = 0.02) while there was no difference between ni-PVR and controls (p = 0.29). CMR data confirmed the echo results, with a significant difference in RV-PA coupling between i-PVR and ni-PVR (RVSV/RVESV 0.9 ± 0.2 vs 1.2 ± 0.3 mL/min/mL, p = 0.01). Conclusions This study shows the presence of worse RV-PA uncoupling, despite normal RV systolic function, in rToF patients with indication to PVR. RV-PA coupling could be a sensitive marker of a progressive maladaptive RV response to long-standing volume overload in rToF prior to the onset of clinical symptoms and RV systolic dysfunction.